Framing of the COVID-19 pandemic: a case study of Norwegian broadcasting news- and debate programs - Solvoll, Mona; Høiby, Marte (MedieKultur: Journal of media and communication research, 2023)
The COVID-19 pandemic has caused both a widespread public health crisis and a global economic crisis, disrupting every aspect of our lives, health, education, jobs, and social life. To provide the public with trustworthy and continuously updated information and stories during uncertain times, newsrooms have made pandemic coverage a priority. Conducting a content analysis of Norwegian news and debate programs on radio and television throughout 2020, we found that the frames most dominant in news broadcasts were the least used frames in debate programs, and vice versa. Overall, the five most common frames were societal consequences, economic consequences, medical risk, government measures, social behaviour, and risk. This suggests that the COVID-19 pandemic was contextualized as an economic and social crisis as well as a health crisis. However, the lack of politicization, conflict and responsibility frames, suggests media coverage missed a critical perspective.